Occupational factors and low back pain: a Mendelian randomization study - Zifeng Wang; Wubing Feng; Qi Jin (Frontiers Media S.A., 2023)
BackgroundLow back pain (LBP) is a common condition and a leading cause of health function loss worldwide. This study assessed the impact of occupational factors on LBP using Mendelian Randomization (MR) method, controlling for confounding variables.MethodsBased on publicly available genome-wide association studies (GWAS), two-sample univariate and multivariate MR analyses were performed to assess the causal effect of occupational factors on LBP. We used the inverse variance weighted (IVW) method and sensitivity analyses to generate the total results for the univariate MR analysis. Furthermore, we performed multivariate MR analysis to assess the direct causal association between occupational factors and LBP after accounting for potential confounding variables.ResultsThe total causal effect of genetically predicted job involves heavy manual or physical work on LBP was found to be significant (IVW OR, 2.117; 95% CI, 1,288-3.479; p = 0.003). Upon adjusting for potential confounding variables, the direct effect of job involves heavy manual or physical work on LBP remained statistically significant. Similarly, the total causal effect of genetically predicted job involves mainly walking or standing on LBP was also found to be significant (IVW OR, 1.429; 95% CI, 1,035-1.975; p = 0.030). However, upon adjusting for potential confounding variables, the direct effect of job involves mainly walking or standing on LBP became insignificant. In contrast, the findings from the MR analysis indicated a lack of association between work/job satisfaction and LBP. Sensitivity analysis consistently supported these trends.ConclusionOur results supported a causal link between job involves heavy manual or physical work and increased risk of LBP, while finding no significant associations between prolonged walking/standing at work, job satisfaction, and LBP, providing valuable insights for the development of targeted prevention and intervention strategies for LBP.